Credit Risk Management in the Commercial Banking Sector: Reflections from a Historical Comparative Study in Nepal - Aryal, Bharat; Aryal, Arjun; Ghimire, Asmita; Manandhar Bajracharya, Shilu (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Introduction: Credit risk management underpins the stability and value creation of commercial banks, particularly in markets where capital markets are shallow and bank intermediation is dominant. This study provides a historical baseline of credit management in Nepal by comparing two large institutions—anonymised as Bank A (majority state-owned commercial bank) and Bank B (private commercial bank with foreign JV origins)—over FY 2006/07–2010/11. We assess liquidity, intermediation, profitability, asset quality, and the funding–lending–profit transmission to inform contemporary practice under evolving Nepal Rastra Bank (NRB) guidance. Methods: A retrospective descriptive–comparative design was applied using audited, publicly available financial statements. Ratio analysis covered liquidity (e.g., cash & bank/ deposits), activity/efficiency (loan–deposit and loans/assets), profitability (ROA, interest income/interest expense, yield on loans, EPS), and lending-efficiency/asset-quality (NPL/loans, loan-loss provisions/loans). Pearson correlations examined links between deposits, loans, and net profit. Names are anonymised to mitigate legal/ethical risk; all figures are reported exactly as in source tables. Results: Liquidity buffers were higher at Bank A (cash & bank/ deposits 0.216 vs 0.063; cash/current deposits 0.948 vs 0.432; cash/savings 0.368 vs 0.172), while both banks’ current ratios averaged <1 (Bank B 0.773, Bank A 0.634). Intermediation intensity was stronger at Bank B (loans/deposits 0.707 vs 0.402; loans/assets 0.610 vs 0.384). Profitability favoured Bank B (ROA 0.023 vs 0.014), though Bank A’s average loan yield was higher (0.164 vs 0.112). Asset quality and risk costs were markedly better at Bank B (NPL/loans 0.012 vs 0.094; LLP/loans 0.003 vs 0.043). Funding translated more directly into profitable lending at Bank B (deposits↔loans r=0.941; loans↔profit r=0.987) than at Bank A (deposits↔loans r=0.631; loans↔profit r=−0.355). Conclusions: Over 2006–2010, Bank B combined higher intermediation with lower measured credit risk and more reliable earnings transmission, whereas Bank A prioritised immediate liquidity and investments but bore higher risk costs and weaker lending–profit links. These contrasts highlight governance, underwriting discipline, and forward-looking provisioning as levers for stronger, more resilient credit management under NRB’s current ECL-aligned regime.